(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2023)
Background: Hypertension in pregnancy is hypertension that occurs when hypertension is first detected in a mother who is known to be normotensive (having normal blood pressure) after 20 weeks of pregnancy without significant proteinuria or other features of preeclampsia.Objective: To know the description of the occurrence of hypertension in pregnant women in the Tumbang Jutuh Health Center UPT area.Method: This research is a type of descriptive research with observational techniques. This design was chosen because the subject was only observed once from data on pregnant women with hypertension in 2022 and variable measurements were carried out at that time. The variables involved in this study were medical history, parity and excess body weight in pregnant women who were experiencing hypertension.Results: The results of identification of the type of disease history of pregnant women were mostly asthma with a total of 15 (37.5%) pregnant women and heart as many as 4 (10%) pregnant women. The results of the identification of parity of primapara pregnant women were 21 (52.5%) pregnant women and multiparous were 19 (47.5%) pregnant women. The results of the identification of normal pregnant women’s weight were 12 (30%) pregnant women, 11 (27.5%) mildly obese pregnant women and 17 (42.5%) pregnant women who were severely obese.Conclusion: The study showed that the incidence of hypertension in pregnant women had hypertension in all of the respondents studied as many as 40 (100%) pregnant women and 0 (0%) pregnant women who did not have hypertension.